2008
DOI: 10.1111/j.1468-1331.2008.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

A 71‐nucleotide deletion in the periaxin gene in a Romani patient with early‐onset slowly progressive demyelinating CMT

Abstract: We identified a novel homozygous mutation c.3286_3356del71 (K1095fsX18) in one Romani patient showing very slow disease progression. Amongst non-Romani Czech CMT patients, PRX mutations have been proven to be very rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Interestingly, 7 of these SNVs were in exon 7, where the majority of known CMT mutations are found. [29][30][31][32][33] However, none of the identified rare variants was reported previously in Mendelian CMT families. We also did not identify compound heterozygous variation in our patients as would be expected in CMT patients.…”
Section: Snvs In Prxmentioning
confidence: 89%
“…Interestingly, 7 of these SNVs were in exon 7, where the majority of known CMT mutations are found. [29][30][31][32][33] However, none of the identified rare variants was reported previously in Mendelian CMT families. We also did not identify compound heterozygous variation in our patients as would be expected in CMT patients.…”
Section: Snvs In Prxmentioning
confidence: 89%
“…The deletion and substitution mutation of the acidic domain establishes loss-of-function mutations in PRX, causing CMT disease. 15,22,23 The self-interaction in L-PRX is blocked by the E1259K mutation in the acidic domain. The amino acid E1259 could be directly involved in the interaction between the NLS and acidic domain; its mutation results in structural L-PRX damage, which possibly causes the E1259K mutation, leading to recessive Dejerine-Sottas neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Deletion mutation of the acidic domain causes Charcot-Marie-Tooth disease, type 4F (CMT4F). 22 PRX mutation analysis in neuropathy patients showed that recessive Dejerine-Sottas neuropathy is caused by R1132G, E1259K, E1359del and R1070X mutations in the acidic domain. 15,23 In this study, a series of N-and C-terminally truncated L-PRX constructs were used to investigate the relationship of the structure and function of L-PRX.…”
Section: Introductionmentioning
confidence: 99%
“…10,18 Several lines of evidence indicated that the periaxin protein's function is directly related to CMT4F disease. 10,18 Several lines of evidence indicated that the periaxin protein's function is directly related to CMT4F disease.…”
Section: Discussionmentioning
confidence: 99%
“…10,18 Several lines of evidence indicated that the periaxin protein's function is directly related to CMT4F disease. 15,18,19 An embryonic age (E) of 13.5 is the earliest time at which Lperiaxin is detectable by immunocytochemistry in the nucleus (adaxonal membrane) of Schwann cells of the mouse PNS. 15,18,19 An embryonic age (E) of 13.5 is the earliest time at which Lperiaxin is detectable by immunocytochemistry in the nucleus (adaxonal membrane) of Schwann cells of the mouse PNS.…”
Section: Discussionmentioning
confidence: 99%